Good corporate governance and its implementation within the company: a systematic literature review - Muhammad Evan Pahlevi (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the trends of previous research and to find out material for further research on Good Corporate Governance (GCG). This research method uses a systematic review of 66 research articles published between 2019 and 2022. Research trends on Good Corporate Governance in terms of research quantity have decreased from 2019 to 2022. Research topics are dominated by research on Corporate Governance, namely 83, 33%. In terms of methods, the trend of research on GCG is more dominated by the panel data regression method. In terms of applied theory, CG research is more dominated by the theory of agency and a combination of stakeholder theory, signaling theory, and legitimacy theory. From the company side, the CG research was dominated by public companies, namely 69.70%. Research on GCG has not examined much about the added value that can be obtained for all parties in the company